PROVIDING FAMILY AS A MAIN AND FIRST ENVIRONMENT FOR THE DEVELOPMENT OF CHILDREN LITERATURE (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The family as the primary and first environment for the development of children's literacy, but the role of the family is rarely explicit so that family members rarely focus on what it does. This article aims to raise awareness that the people closest to the child will determine literacy skills especially reading. This article is based on literature review that has been done by the author from various sources as a material to give explanation about empowering family to child literacy development. In addition, data is collected through interviews to parents who have given a role in developing children's literacy skills. The strategy to empower families in this article refers to Roskos, et al (2003) suggests 8 strategies that can be done in the school environment. But only 4 strategies are taken in this article because it is considered in accordance with the purpose and can be implemented in the home environment (1) rich teacher talk; (2) reading a story book; (3) alphabetical activity; (4) support the occurence of reading.